A MALAYSIAN PERSPECTIVE ON DECOLONIZATION: LESSONS FOR INDONESIA? - J. Thomas Linbald (Masyarakat Indonesia, 2013)
The great regime change in Indonesian history, represented by independence anddecolonization, had profound implications for the state apparatus, in particular in itsrelationship to the economy. This contribution seeks to widen our perspective on suchchange in Indonesia by reviewing evidence from the experience of adjacent Malaysia.Particular attention is given to the indigenization of the government bureaucracy -Indonesianisasi in Indonesia, Malayanization in Malaysia - before as well as in theimmediate aftermath of independence. Our findings underscore the recent consensusin the international literature that the way in which the process of decolonizationoccurred had enormous consequences for subsequent performance. This article arguesthat Indonesia could have reaped considerable benefit if in a position to apply theMalaysian model of indigenizing the institution of the state.Keywords: Decolonization, Indigenization, Malayanization, Indonesianisasi